A nutritional supplement based on a synbiotic combination of Bacillus subtilis DSM 32315 and L-alanyl-L-glutamine improves glucose metabolism in healthy prediabetic subjects – A real-life post-marketing study - Kordowski, Anna; Tetzlaff-Lelleck, Vivian Valeska; Speckmann, Bodo; Loh, Gunnar; Künstner, Axel; Schulz, Franziska; Schröder, Torsten; Smollich, Martin; Sina, Christian; tom Dieck, Heike (Frontiers in Nutrition, 2022)
Impaired glucose homeostasis is a significant risk factor for cardiometabolic diseases, whereas the efficacy of available standard therapies is limited, mainly because of poor adherence. This post-marketing study assessed the glucose-lowering potential of a synbiotic-based formulation. 192 participants were enrolled in a digital nutrition program with continuous glucose monitoring (CGM) and received a study product comprising Bacillus subtilis DSM 32315 and L-alanyl-L-glutamine. Participants underwent a first sensor phase without supplementation, followed by a 14-day supplementation phase without sensor, and completed by a second sensor phase while continuing supplementation. Fasting glucose levels were determined before and after supplementation by CGM. In addition, the postprandial glycemic response to an oral glucose challenge, body weight, HbA1c concentrations, and BMI were analyzed. Subgroup analyses of subjects with elevated glucose and HbA1c levels vs. normoglycemic subjects were performed. Supplementation with the study product resulted in significant improvements in glucose parameters (delta values: fasting glucose -2,13 % ± 8.86; iAUC -4.91 % ± 78.87; HbA1c: -1.20 % ± 4.72) accompanied by a significant weight reduction (-1.07 kg ± 2.30) in the study population. Subgroup analyses revealed that the improvements were mainly attributed to a prediabetic subgroup with elevated fasting glucose and HbA1c values before supplementation (delta values: fasting glucose -6.10 % ± 7.89; iAUC -6.28 % ± 115.85; HbA1c -3.31 % ± 4.36; weight: -1.47 kg ± 2.82). In conclusion, this study indicates that the synbiotic composition is an effective and convenient approach to counteract hyperglycemia. Further placebo-controlled studies are warranted to test its efficacy in the treatment of cardiometabolic diseases.